Efficiency Assessment of Selected Indonesian Food and Beverage Manufacturing Industry - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Efficient use of resources to generate outputs in food and beverage manufacturing industry is critical. This research evaluates the revenue, net income, fixed assets and operating expenses of five Indonesian food and beverage manufacturing companies. It presents a study which demonstrates how managers can identify the best performers in the industry and how to conduct an improvement analysis using data envelopment analysis (DEA) approach. Data on five food and beverage manufacturing companies collected from Jakarta Stock Exchange were used to identify inefficient companies and determine which efficient companies to benchmark in order to improve their efficiency. Findings show that the efficient companies have reached the input and output target. The emphasis of this paper is on the application.   Efficient use of resources to generate outputs in food and beverage manufacturing industry is critical. This research evaluates the revenue, net income, fixed assets and operating expenses of five Indonesian food and beverage manufacturing companies. It presents a study which demonstrates how managers can identify the best performers in the industry and how to conduct an improvement analysis using data envelopment analysis (DEA) approach. Data on five food and beverage manufacturing companies collected from Jakarta Stock Exchange were used to identify inefficient companies and determine which efficient companies to benchmark in order to improve their efficiency. Findings show that the efficient companies have reached the input and output target. The emphasis of this paper is on the application.   Efficient use of resources to generate outputs in food and beverage manufacturing industry is critical. This research evaluates the revenue, net income, fixed assets and operating expenses of five Indonesian food and beverage manufacturing companies. It presents a study which demonstrates how managers can identify the best performers in the industry and how to conduct an improvement analysis using data envelopment analysis (DEA) approach. Data on five food and beverage manufacturing companies collected from Jakarta Stock Exchange were used to identify inefficient companies and determine which efficient companies to benchmark in order to improve their efficiency. Findings show that the efficient companies have reached the input and output target. The emphasis of this paper is on the application.   Efficient use of resources to generate outputs in food and beverage manufacturing industry is critical. This research evaluates the revenue, net income, fixed assets and operating expenses of five Indonesian food and beverage manufacturing companies. It presents a study which demonstrates how managers can identify the best performers in the industry and how to conduct an improvement analysis using data envelopment analysis (DEA) approach. Data on five food and beverage manufacturing companies collected from Jakarta Stock Exchange were used to identify inefficient companies and determine which efficient companies to benchmark in order to improve their efficiency. Findings show that the efficient companies have reached the input and output target. The emphasis of this paper is on the application.